Low canopy temperature and high stomatal conductance contribute to high grain yield of contrasting japonica rice under aerobic conditions - Gong, Wenliu; Proud, Christopher; Fukai, Shu; Mitchell, Jaquie (Frontiers in Plant Science, 2023)
Water limitation is a major concern in rice production. It has been suggested that with adapted genotypes, aerobic rice production offers the maintenance of grain yield while saving water. However, there has been limited exploration of Japonica germplasm adapted for high yield aerobic environments. Therefore, three aerobic field experiments with different levels of relatively high-water availability were conducted across two seasons to explore genetic variation in grain yield and physiological traits that contributed to high yield. In the first season, a Japonica rice diversity set was explored under well-watered (WW20) conditions. While in the second season, a well-watered (WW21) and intermittent water deficit (IWD21) experiment were conducted to examine the performance of a subset of 38 genotypes selected for low (mean of -6.01 °C) and high (mean of -8.22 °C) canopy temperature depression (CTD). In WW20, CTD explained 19% of the variation in grain yield which was similar to the variation explained by plant height, lodging and leaf death response to heat. In WW21 a relatively high average grain yield (8.99 t ha-1) was achieved, while a 23% reduction was achieved in IWD21. Compared to the low CTD group, the high CTD group had 21% and 28% higher stomatal conductance, 32% and 66% higher photosynthetic rate, and 16% and 29% higher grain yield in the WW21 and IWD21, respectively. This work demonstrated the advantage of higher stomatal conductance and cooler canopy temperature which resulted in higher photosynthetic rate and higher grain yield. Two promising genotypes with high grain yield, cooler canopy temperature and high stomatal conductance were identified as donor genotypes for use by the rice breeding program when aerobic rice production is a target. Field screening for cooler canopies within a breeding program with high-throughput phenotyping tools would be of value for genotype selection for aerobic adaption.